2020
DOI: 10.1371/journal.pone.0226930
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographic study of human gut-associated crAssphage suggests impacts from industrialization and recent expansion

Abstract: CrAssphage (cross-assembly phage) is a bacteriophage that was first discovered in human gut metagenomic data. CrAssphage belongs to a diverse family of crAss-like bacteriophages thought to infect gut commensal bacteria belonging to Bacteroides species. However, not much is known about the biogeography of crAssphage and whether certain strains are associated with specific human populations. In this study, we screened publicly available human gut metagenomic data from 3,341 samples for the presence of crAssphage… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 55 publications
0
33
0
Order By: Relevance
“…In humans, the relative abundance of this phage family in the gut can be as high as 90% of the total viral load in some individuals. The geographical spread of this phage family has also been confirmed with p-crAssphage for example, being largely absent from hunter-gatherer gut populations compared to industrialized populations [ 19 , 22 24 ]. This may be due to differences in dietary habits and bacteriome compositions.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the relative abundance of this phage family in the gut can be as high as 90% of the total viral load in some individuals. The geographical spread of this phage family has also been confirmed with p-crAssphage for example, being largely absent from hunter-gatherer gut populations compared to industrialized populations [ 19 , 22 24 ]. This may be due to differences in dietary habits and bacteriome compositions.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of geographical variation in crAssphage concentrations, Farkas et al (2019) found lower, but still measurable, concentrations of crAssphage in WWTP influent in the United Kingdom than were found in Tampa, Florida (Ahmed et al 2018b), andSpain (García-Aljaro et al 2017). Geographic differences in crAssphage concentrations in untreated sewage had been noted in earlier studies (Stachler and Bibby 2014), potentially due to geographic differences in viral distributions (Stachler and Bibby 2014), levels of industrialization, or diet (Honap et al 2020).…”
Section: Crassphagementioning
confidence: 69%
“…Neither wastewater treatment capacity nor wastewater volume received affected the concentrations of HPyVs and crAssphage, as previously stated (Crank et al, 2020). However, differences in reported quantity could result from intrinsic factors, such as different gut microbial levels due to diets and lifestyles (Honap et al, 2020; Mah et al, 2008; Turnbaugh et al, 2009), and extrinsic factors, such as temperature, sewer pipe condition, and retention time (Ahmed et al, 2019c; Okadera et al, 2020). Comparisons among different studies could also present confounding biases due to different field and laboratory protocols, analytical instruments, and data analysis methods, which could affect each virus at different levels (Agetsuma-Yanagihara et al, 2017; Crank et al, 2020; Kongprajug et al, 2020; Petcharat et al, 2020; Shanks et al, 2012).…”
Section: Discussionmentioning
confidence: 99%